Housing First Combined with Suicide Treatment Education and Prevention (HOME + STEP): study protocol for a randomized controlled trial - Laura Chavez; Kelly Kelleher; Alicia Bunger; Brittany Brackenoff; Ruri Famelia; Jodi Ford; Xin Feng; Allen Mallory; Jared Martin; Arielle Sheftall; Laura Walsh; Tansel Yilmazer; et al. (BMC, 2021)
Abstract Background Youth experiencing homelessness are at high risk for suicide, yet few studies have evaluated risk reduction interventions targeting suicidal ideation in this vulnerable population. A comprehensive approach to risk-reduction is needed that addresses basic needs and provides targeted interventions for those at highest risk. The protocol described builds on the design of the first randomized trial of Housing First (HF) for homeless youth. The primary objective is to determine whether housing combined with supportive services that include suicide screening and targeted psychotherapy (Cognitive Therapy for Suicide Prevention) is effective for reducing suicidal ideation and other secondary outcomes (depression and suicide attempts). Additionally, we will explore mediators of the treatment effect (housing stability and substance use) and determinants of implementation. Methods Youth recruited to the HF trial will be randomized to HF + supportive services (n = 120), or supportive services alone (n = 120). The "Suicide Treatment Education and Prevention" (STEP) protocol will additionally screen youth in both arms at baseline and 3 months for suicidal ideation (SSI-W). Those who screen as moderate risk for suicide (SSI-W ≥ 10) will be offered CTSP, which includes up to 9 sessions over the first 6 months following enrollment. CTSP will be delivered in one-on-one sessions by a trained advocate. Research assessments will be collected to assess outcomes (including suicidal ideation) at baseline, 3, 6, 9 and 12 months. Qualitative interviews with subjects receiving CTSP and other stakeholders will explore implementation determinants. Discussion The study will fill an important gap in the literature about the added benefit of HF combined with supportive services including suicide screening and treatment for reducing suicidal ideation in homeless youth. With the urgent need to address both homelessness and suicide risk, evidence is needed about services that can be integrated into delivery settings for youth experiencing homelessness. Trial registration NCT04135703 . Date of registration: October 23, 2019.